FAKTOR PENGHAMBAT MINAT NASABAH DALAM MENGGUNAKAN SISTEM LAYANAN PERBANKAN BERBASIS MOBILE BANKING (Studi Kasus pada Mahasiswa Angkatan 2012-2014 Fakultas Ekonomi dan Bisnis, Universitas Brawijaya, Malang) - Anggara, Satria (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to learn about the factors that inhibit customers' interest in using mobile banking services. The study was conducted on students batch 2012-2014 of the Faculty of Economics and Business, Brawijaya University. Factors included in this study is the lack of information, cost, tradition, and the complexity of registration. The model used in this study is Partial Least Square (PLS). PLS oriented to predictions, clarify whether there is any relationship, and confirm the theory. Based on these test results showed that factors of limited information, the traditions, and the complexity of the registration proved to be an hindering factors of interest in the use of mobile banking services, while the cost factor proved not to be an hindering.Keywords: mobile banking, information, cost, tradition, complexity of registration, hindering factor